Opening new frontiers with catalytic nucleic acids in miRNA inhibition - Patutina, Olga; Miroshnichenko, Svetlana; Chiglintseva, Daria; Zenkova, Marina (Frontiers in Pharmacology, 2025)
The concept of utilizing synthetic nucleic acids and their conjugates with biologically active molecules as RNA-targeted therapeutic agents represents a powerful strategy in the treatment of human pathologies. Recent research demonstrates that neoplastic development is closely associated with dysregulation of miRNAs, which are essential regulators of gene expression, highlighting the potential of therapeutic strategies aimed at their inhibition. Current approaches to pathological microRNA (miRNA) regulation primarily rely on physical blocking or sequestration mechanisms. However, these non-enzymatic strategies are limited by their stoichiometric nature, necessitating high drug doses to achieve therapeutic efficacy. A promising alternative lies in the application of catalytic nucleic acids, including miRNA-targeted ribozymes, DNAzymes/XNAzymes (antimiRzymes), and artificial ribonucleases (miRNases), which enable selective suppression of overexpressed miRNAs in pathological conditions through multiple enzymatic cleavage events. This review examines the fundamental principles governing the design of currently developed antimiRzymes and miRNases, analyzes their ribonuclease activity using synthetic miRNA substrates, and discusses key achievements in miRNA-inhibiting capability in tumor cells, along with their antitumor effects. Being effective RNA cleavers, these catalytic nucleic acids demonstrate remarkable potential, often surpassing the efficacy of conventional antisense oligonucleotides, and represent a promising therapeutic modality for RNA-associated diseases.